Peran Keluarga dalam Menumbuhkan Kepercayaan Diri Anak - Anna Sari Hasibuan; Laila Sari; Suci Amelia; Farel Febriananda; Hidayani Syam (JOURNAL SAINS STUDENT RESEARCH, 2025)
The family is the earliest and most important institution in a person's life. The role of the family is very important in shaping character and influencing children's development. The family has a responsibility to provide education to their children. In the family environment, children learn about the values, norms, and behaviors accepted in society. Parents act as the main models/role models in shaping children's character, teaching them about the world, helping them learn to read, write, and develop other knowledge and skills. By providing good education, families encourage children's growth and development in various aspects of life. Emotional and psychological support is important for children's development. When children feel loved, accepted, and supported by their families, they feel safe and confident. Adequate attention and affection help children develop positive self-esteem and overcome challenges in life. In a harmonious family environment, children feel comfortable sharing their feelings.